171 Effects of Dietary Valine, Isoleucine, and Tryptophan Supplementations to Diets Containing Excess Leucine on Nitrogen Balance of Growing Pigs. (7th May 2021) - Kwon, Woongbi Bi; Soto, Jose A; Stein, Hans H
Abstract: An experiment was conducted to test the hypothesis that increasing concentrations of dietary Val, Ile, or Trp alone or in combination will alleviate negative effects of excess dietary Leu on N balance of growing pigs. Seventy-two barrows (initial body weight: 33.9 ± 2.6 kg) were housed in metabolism crates and randomly assigned to 1 of 8 diets and 3 blocks with 3 pigs per diet in each block in a 12-d experiment. Treatments were arranged in a 2 × 2 × 2 factorial with the main effects of L-Val (0 or 0.1%), L-Ile (0 or 0.1%), and L-Trp (0 or 0.05%) that were added to a basal diet containing corn and a high-protein corn product (48% crude protein; 5.9% Leu). The basal diet contained 1.00 % standardized ileal digestible (SID) Lys and 171% SID Leu:Lys. Data were analyzed using the PROC MIXED of SAS with concentrations of Val, Ile, and Trp, and all interactions as main effects and replicate as a random effect. No 3-way interactions were observed (Table 1). Results indicated that fecal N output increased if Ile was added to diets without added Val, but that was not the case if Val was added (interaction, P < 0.05). Addition of Ile to diets reduced N retention, but N retention increased with Trp addition to diets without Val addition, but not if Trp was added to diets with added Val (interaction, P < 0.05). The biological value of protein increased if Trp was added to diets without addition of Ile, but if Ile was added, Trp addition did not increase the biological value of protein (interaction, P < 0.05). In conclusion, adding Ile to a diet with excess Leu reduced N retention, but if Trp was added alone or in combination with Ile or Val, N retention increased.